Predictors of Nursing Staff Voluntary Termination in Nursing Homes: A Case-Control Study. (November 2019) - Zhang, Yuan; Punnett, Laura; Gore, Rebecca
Workforce instability in the long-term care sector has raised wide attention about nursing staff turnover. Most attention has been devoted to understanding the relationship between facility's characteristics and organizational turnover. This case-control study examined the contribution of work characteristics to individual staff turnover. Surveys were collected with nursing staff in 18 for-profit nursing homes on up to five occasions between 2006 and 2012. A list of nursing staff voluntarily terminating jobs was provided by the company. Cases and controls (628 of each) were selected from survey respondents by matching on age, job category, and survey occasion. Multiple predictor conditional logistic regression models showed that evening shift work (hazards ratio [HR] = 2.00, p < .01) and shift length > 8 hr (HR = 1.42, p < .05) were contributing factors to voluntary termination. This study provides different perspectives of nursing staff voluntary termination in nursing homes. Future qualitative research would be valuable to explore and understand nursing staff turnover in the health care industry.